Analysis of the Stress Experienced by Nurses Working in the Operations and the Factors Causing It - Mickienė, Nijolė; Surgunt, Natalja; Mikaliūkštienė, Aldona (Slauga. Mokslas ir praktika, 2024)
Employees working in the operating rooms experience some of the highest levels of stress in their profession. Representatives of this profession have to meet many requirements: to possess good professional skills, consistently attend to patients‘ needs, , to provide qualified nursing care , to be able to work in a team and to be able to use highly specialized, modern and innovative technologies. The aim of the work is to analyze scientific literature on the stress experienced by nurses working in operating room and the contributing factors. The search for scientific literature using keywords was carried out in October–December 2023 in the international PubMed database and the specialized information retrieval system Google Scholar. The systematic review included 31 articles on the subject. Analysis of these scientific publications revealed various stressors for operating room nurses, including physical, chemical, biological, and psychosocial factors.. Operating room nurses often experience stress due to the complicated work process, poor psychological climate, heavy workload, inadequate remuneration, and night work. Factors such as unpredictable and stressful nature of surgical procedures, lack of necessary tools or technical malfunctions, high workload, and understaffing are all contributors to professional stress among operating room personnel.